Imaging of healthy and malaria-mimicked red blood cells in polydimethylsiloxane microchannels for determination of cells deformability and flow velocity - Vilas Boas, Liliana (2018)
Imaging analysis techniques have been extensively used to obtain crucial information on blood phenomena in the microcirculation. In the present study, it is intended to mimic the effects of malaria on the red blood cells (RBCs), by changing their properties using a different concentration of glutaraldehyde solution. The effects of the disease in stiffing RBCs were evaluated using polydimethylsiloxane microchannels that comprise contractions with 10 µm width and measuring the cells deformability and the flow velocity in healthy and modified conditions. The obtained results show a decrease in the RBCs deformability and in the flow velocity with the presence of glutaraldehyde, when compared to the behavior of healthy RBCs samples. Therefore, it can be concluded that, using image analysis (ImageJ & PIVLab), it is possible to measure the deformability of the RBCs and the flow velocity and, consequently, obtaining a correlation between the difference of velocities/deformabilities in the microchannels. In the future, this correlation can be used to relate the RBCs behavior with the various stages of malaria. This study can be a starting point for establishing the development of new malaria diagnostic systems towards point-of-care lab-on-a-chip devices.